Tinjauan Pelaksanaan Pengaspalan AC-BC Pada Proyek Rekonstruksi Jalan Air Pinang – Ujung Batee Kecamatan Tapaktuan – Pasie Raja Kabupaten Aceh Selatan - Suryana, Intan; Chaira, Chaira; Refiyanni, Meidia (Rifa'Institute, 2022)
The planning of the Air Pinang - Ujung Batee road reconstruction project, Tapaktuan - Pasie Raja District, South Aceh Regency is a step to meet road comfort, efficiency and also increase road users. The importance of the review as part of the evaluation and supervision as well as a source of data for other researchers in order to support the smooth and fast transportation and economy as well as increase the ease of access for the community, especially in the Air Pinang area. In this research method, the researcher uses qualitative methods, where this research starts from data collection, where in this study primary data is used, namely data obtained from respondents through interviews, direct observation, while secondary data is obtained from journals, articles and also from relevant company data. The results of the analysis show that the process of carrying out the work is good, starting with preparing the road body and then laying it compacted using a vebrator roller, after the compaction process is complete, the binder absorption layer is carried out, namely liquid asphalt is sprayed with asphalt sprayer.